The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/dme.14189
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes self‐management education exposure and glycated haemoglobin levels among Marshallese participants in a randomized controlled study

Abstract: Aims A randomized control trial (RCT) of diabetes self-management education (DSME), undertaken by a communitybased participatory research (CBPR) partnership between the University of Arkansas for Medical Sciences (UAMS) and the Marshallese community in Arkansas. The RCT examined the effect of hours of intervention exposure, with the hypothesis that increased exposure is one reason the Adapted-Family DSME was found to be more effective than the Standard DSME.Methods Some 221 Marshallese with type 2 diabetes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…The team includes more than 20 Marshallese staff members working at the university and communitybased organizations, Marshallese nurses, and a Marshallese physician. It is led by a community advisory board and include subcontracts to several nonprofit organizations led by Marshallese people (44,47,49,50). The partnership was funded by a CDC program, Racial and Ethnic Approaches to Community Health (REACH).…”
mentioning
confidence: 99%
“…The team includes more than 20 Marshallese staff members working at the university and communitybased organizations, Marshallese nurses, and a Marshallese physician. It is led by a community advisory board and include subcontracts to several nonprofit organizations led by Marshallese people (44,47,49,50). The partnership was funded by a CDC program, Racial and Ethnic Approaches to Community Health (REACH).…”
mentioning
confidence: 99%
“…Family members can monitor the behavior of patients' diabetes education course learning through the family portal, and the study by McElfish et al [19] has revealed that family-model diabetes self-management education shows better effects than standard diabetes self-management education [19]. The family-model can increase the time of exposure to diabetes self-management education, and increased time of exposure to leads to improved glycemic control in patients [20]. The diabetes education courses on the LCCP platform cover patients' self-care behaviors according to the American Association of Diabetes Educators 7 Standard of Care.…”
Section: Principal Findingsmentioning
confidence: 99%
“…Family member engagement in diabetes self-management education programs can improve patients' self-management behaviors, quality of life, and glycemic control [16][17][18]. Studies have also shown that family-model diabetes self-management education is superior to conventional diabetes education that only involves patients [19,20]. However, family members, especially young members, cannot always participate in diabetes management programs that require onsite visits for long periods of time [11].…”
Section: Introductionmentioning
confidence: 99%
“…The intervention was delivered in primary participants' homes by a bilingual CHW with a certified diabetes educator (CDE) present. The F-DSMES demonstrated effectiveness compared with standard DSMES delivered by CDEs in a group setting [ 31 , 32 ]; however, the methods used in this previous trial may not be directly transferable to the RMI. The RMI lacks the resources to deliver standard DSMES effectively due to a lack of CDEs in the RMI.…”
Section: Introductionmentioning
confidence: 99%